Effects of Fertilizer on Growth and Biomass Allocation of Three Evergreen Tree Species from Seasonally Dry Tropical Forests - Shannon, Dia Panitnard; Tiansawat, Pimonrat; Dasoon, Sirinapa; Elliott, Stephen; Pheera, Wittaya (Trends in Sciences, 2023)
Tree planting is widely accepted as a strategy to mitigate climate change, with a strong focus on use of native tree species. Various kinds of fertilizer have been recommended to produce optimal quality planting stocks for forest restoration. This study tested the hypothesis that additional fertilizer could improve seedling growth and alter biomass allocation in seedlings of evergreen tree species. Three species were studied: Aphanamixis polystachya (a slow-growing species), Eriobotrya bengalensis (a pioneer species) and Podocarpus neriifolius (a slow-growing species). These species are used to restore seasonally dry tropical forests in northern Thailand. We applied 4 different treatments of fertilizer addition (0, 150, 300 and 600 mg per seedling) and measured relative growth rate (RGR) and biomass allocation. The 3 species responded differently to the fertilizer addition in both growth and biomass allocation. Only the pioneer species, E. bengalensis, showed a significant response to fertilizer addition at the highest dose. The 600 mg treatment increased E. bengalensis’ RGR by 60 % but decreased root mass fraction by 4 %, compared with the control. Pioneer species respond to fertilizer addition with accelerated growth rate rather than by increasing nutrient stores. On the other hand, slow-growing species have a low annual requirement; therefore, they are not highly responsive to nutrient addition. Further investigation into the effects of fertilizer on growth and biomass allocation in pioneer species is needed to enable the propagation of cost-effective and high-quality planting stocks for forest restoration. HIGHLIGHTS The effect of four different amounts of fertilizer (0, 150, 300 and 600 mg) on growth and biomass allocation was investigated in three native tree species from northern Thailand - Aphanamixis polystachya, Eriobotrya bengalensis and Podocarpus neriifolius The three species responded differently to the fertilizer in both growth and biomass allocation While the addition of 600 mg of fertilizer increased the relative growth rate of bengalensis, a pioneer species, by 60 %, fertilizer addition did not affect the growth rate of relatively slow-growing species - A. polystachya and P. neriifolius The root mass fraction of the pioneer species was reduced by 4 % in the 600 mg fertilizer treatment compared with the control treatment, while the biomass allocation of the relatively slow-growing species was not affected by the fertilizer GRAPHICAL ABSTRACT